2007
DOI: 10.1523/jneurosci.1866-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of TRPV1 by Phosphoinositides

Abstract: . These data show that at low capsaicin concentrations and other moderate stimuli, PtdIns(4,5)P 2 partially inhibits TRPV1 in a cellular context, but this effect is likely to be indirect, because it is not detectable in excised patches. We conclude that phosphoinositides have both inhibitory and activating effects on TRPV1, resulting in complex and distinct regulation at various stimulation levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
363
4
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(397 citation statements)
references
References 52 publications
27
363
4
2
Order By: Relevance
“…31 High frequency calcium fluxes at the membrane result from increased channel opening events alone. TRP channel opening frequency is reportedly controlled by PIP2 [59][60][61][62] and inhibited by calmodulin. 59,[63][64][65] Studying these proteins in context of growth factor-stimulated calcium influx and EMT may be of interest.…”
Section: Molecular Control Of Calcium Influxes Upon Induction Of Epitmentioning
confidence: 99%
“…31 High frequency calcium fluxes at the membrane result from increased channel opening events alone. TRP channel opening frequency is reportedly controlled by PIP2 [59][60][61][62] and inhibited by calmodulin. 59,[63][64][65] Studying these proteins in context of growth factor-stimulated calcium influx and EMT may be of interest.…”
Section: Molecular Control Of Calcium Influxes Upon Induction Of Epitmentioning
confidence: 99%
“…PI(4,5)P 2 has been proposed to inhibit TRPV1, mediating the sensitizing actions of bradykinin and nerve growth factor (Chuang et al, 2001;Cao et al, 2013a). In contrast, others (including us) have proposed that PI(4,5)P 2 activates TRPV1 (Stein et al, 2006;Lukacs et al, 2007Lukacs et al, , 2013aKlein et al, 2008), and the depletion of PI(4,5)P 2 by phospholipase C may play a role in Ca 2+ -dependent desensitization (Mercado et al, 2010;Lukacs et al, 2013b). However, a recent study measured the apparent affinity of TRPV1 for diC8-PI(4,5)P 2 and found that the activating effects occurred with a K 1/2 of only 0.03 mol % in the plasma membrane, raising the question of whether PI(4,5)P 2 levels in the plasma membrane ever get sufficiently low selectivity must involve multiple, specific inter actions between TRPV1 and the phosphoinositide ligand.…”
Section: Discussionmentioning
confidence: 98%
“…The crystal structure of GIRK2 bound to PI(4,5)P 2 shows a structured binding pocket in which several hydrogen bonds are formed between basic residues in the protein and both the 4 and 5 phosphates (Whorton and MacKinnon, 2011). Based on this structure, it seems reasonable to predict that GIRK2 might display some phosphoinositide Mechanism for phosphoinositide selectivity and activation of TRPV1 ion channels the response of pain receptor neurons to noxious stimuli, disagreement about whether PI(4,5)P 2 activates or inhibits TRPV1 continues (Chuang et al, 2001;Prescott and Julius, 2003;Stein et al, 2006;Lukacs et al, 2007Lukacs et al, , 2013a; Ufret-Vincenty et al, 2011;Cao et al, 2013a,b;Senning et al, 2014). There is also disagreement about whether PI(4,5)P 2 interacts directly with TRPV1 or acts via the integral membrane protein Pirt (Kim et al, 2008;Ufret-Vincenty et al, 2011).…”
mentioning
confidence: 98%
“…Indeed, bradykinin [183,184], ATP [185], lipoxygenase products [182,183], prostaglandins [186,187], histamine [188], various neurotrophins (NGF, neurotrophin-3 and -4) [91,102,184], TNF- [189,190], pro-inflammatory chemokines [191], and PAR2 [192,193] were all reported to sensitize TRPV1 via various signal transduction pathways. TRPV1 was shown to be modulated by the protein kinase C (PKC) [183,[194][195][196], phospholipase C (PLC), and phosphatidylinositol 4,5-bisphosphate (PIP 2 ) [184,[197][198][199][200] systems as well as by intracellular ATP [201]. The sensitization process eventually results in the shift of the activation temperature and voltage threshold towards more physiological ranges [195,[202][203][204].…”
Section: Activation and Sensitization Of Trpv1mentioning
confidence: 99%